Using Storytelling Technique in Improving Speaking Skill of Grade Eight Students of SMP Negeri Model Terpadu Madani Palu - Munira Ria Rezky; R. Mertosono, Sudarkam; Lebagi, Desrin; Darmawan, Darmawan (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2024)
This research aims to discover whether using storytelling technique can improve the speaking skill of the grade eight students of SMPN Model Terpadu Madani Palu. This research implemented quasi experimental design. The population is 153 students. The sample is 60 students of classes VIII Ki Hajar Dewantara and VIII Raden Saleh which were selected by employing cluster random sampling technique. To collect the data, test which was divided into pretest and posttest were used as the research instrument. The data were processed using SPSS 22. The findings revealed that students’ speaking skill improve after got the treatment. Based on the calculation, the mean score of experimental class (65.83) is higher than the mean score of control class (60.27). It is also supported by data analysis using independent sample t-test, it showed that the p-value (sig.) is lower than the chosen alpha level (0.000 < 0.05). In conclusion, the alternative hypothesis is accepted or using storytelling technique effectively improves students speaking skill of grade eight of SMP Negeri Model Tepadu Madani Palu.